Analysis of the Kastengel Quality Produced From the White Sweet Potato Flour - Meri Rahmadani; Rahmi Holinesti (Universitas Negeri Padang, 2021)
Kastengel is a cookie from the Netherlands that is crunchy, contains cheese, these cookies are in the form of blocks with a size of 4x1x1 cm, golden yellow, and fragrant. Kastengel is made from the main ingredient in the form of wheat flour which is still imported. The development of products from local flour, such as white sweet potato flour can reduce imports of wheat flour. The nutritional content of white sweet potato is not inferior to wheat and is widely grown in West Sumatra. This study discusses the analysis of the quality (shape, color, aroma, texture, and taste) of white sweet potato flour kastengel as much as 15%, 30%, and 45%. A true experiment is this type of research with completely randomized design (CRD) method, three replications, and three treatments. Data were obtained directly from 5 panelists who answered a questionnaire (sensory test format) about the quality of white sweet potato flour kastengel which was referred to as primary data. Then tabulate the data obtained in tabular form and perform analysis of variance (ANOVA). If the analysis of variance shows Fcount>Ftable, proceed to Duncan's test. The results showed that the color (golden yellow) and texture (crispy) of white sweet potato flour had a significant effect on the quality of kastengel. The result of the best quality of white sweet potato flour kastengel was the substitution of 30% white sweet potato flour in the treatment (X2).